(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To summarize evidence and provide an overview of the prevalence of H. pylori reinfection and describe some associated factors. Subject and method: This scoping review was conducted by systematically searching PubMed, Cochrane Library, and Google Scholar for relevant studies published up to May 2024. Additional records were identified through manual reference checks. Studies were screened based on inclusion and exclusion criteria, and key data were extracted and synthesized narratively. Results: A total of 40 studies were included, reporting annual reinfection rates of H. pylori that ranged from 0.8% to 29.8%, with higher rates observed in developing regions. Factors associated with reinfection included young age, low socioeconomic status, crowded living conditions, household exposure to infected individuals, poor hygiene practices, specific treatment regimens, and comorbidities. Preventive interventions reported in the literature encompassed hygiene education, community-based screening, and adjustments to eradication regimens. Conclusion: H. pylori reinfection remains a significant public health concern, particularly in low-resource settings. Effective and context-specific preventive strategies are crucial to improving long-term eradication outcomes.